COMPLEX APPROACH TO THE MATTERS O F INCREASE OF THE MAIN AND AUXILIARY EQUIPMENT OPERATION RELIABILITY AT RUP “BMZ” - A. N. Katsyn (Литьë и металлургия)
The matters of increase of the main and auxiliary equipment at RUP "BMZ" are considered.